Letter Identity and Phonemic Processing in Word Comparison: their relative ordering - Thurston, Munro Ian (My University, 1974)
The view of some is that people process printed words in a highly flexible fashion, attending to now this characteristic of a word, now that, as the task demands it. This thesis, after discussing some models of the types of information in words and the relationships among these types of information and their processing, reports experiments showing three different effects which demonstrate that there are restrictions on the ways in which information about the appearance of letters and their identity is processed relative to information about the phonology or pronunciation of the words. These limitations are explained in terms of a model in which phonemic information becomes available completely at a later time than visual features or the identity of letters in a word. It is argued that the most likely form of this model is one in which visual features and letter-identity become available as a result of the operations of an early processing stage or stages, while phonemic information becomes available as a result of the operation of a subsequent stage, the input of which is the output of the first.
Keywords: Psychology; Psychology